2012
DOI: 10.20885/jsb.vol16.iss1.art7
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penganggaran Partisipatif terhadap Kinerja Manajerial dengan Budaya Organisasi dan Gaya Kepemimpinan sebagai Variabel Moderating

Abstract: This study aimed to exam the effect of participatory budgeting on managerial performance in wich organizational culture and leadership styles as moderating variabel. This research used moderating regression analysis (MRA) to test the proposed. The survey was conducted on 144 personnel involved in the budgeting process from local government. The results of this study demonstrated that participatory budgeting interaction with organizational culture and leadership style is positively related to managerial perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 14 publications
2
8
0
7
Order By: Relevance
“…According to psychological theory, participatory budgeting has a positive effect on performance through motivational and cognitive mechanisms (Birnberg & Luft, 2007). This is in line with the study of Soleman (2012). Whereas Yusnaini (2010) found that nonparticipatory budgets cause low performance when the target and the process of determining the budget are done unfairly.…”
Section: Article Classificationsupporting
confidence: 52%
“…According to psychological theory, participatory budgeting has a positive effect on performance through motivational and cognitive mechanisms (Birnberg & Luft, 2007). This is in line with the study of Soleman (2012). Whereas Yusnaini (2010) found that nonparticipatory budgets cause low performance when the target and the process of determining the budget are done unfairly.…”
Section: Article Classificationsupporting
confidence: 52%
“…Performance is interpreted as a level to meet expectations associated with its function [19]. This expectation is related to its function in the organization.…”
Section: Performancementioning
confidence: 99%
“…Keberhasilan dalam mengelola suatu organisasi tidak lepas dari faktor budaya organisasi (Soleman, 2012). Menurut Hartidah dan Ludigdo (2010) budaya memiliki pengaruh yang besar terhadap keseluruhan organisasi, mempengaruhi praktek dari semua aspek organisasi, dan mempengaruhi kesuksesan organisasi.…”
Section: Pendahuluanunclassified